DECIPHERING E-COMMERCE: TYPES, EFFECTS, AND TRANSACTIONAL DYNAMICS - Dilafruz Sodiqova Zoxid qizi (American Journals, 2024)
This article delves into e-commerce, analyzing its types, effects, and transactional dynamics in today’s digital world. It explores six key categories, from B2B to C2A, highlighting benefits for consumers and sellers and addressing challenges like market growth and cybersecurity risks. Additionally, it examines the evolving transaction process and its impact on businesses and consumers, emphasizing e-commerce’s crucial role in driving global trade and economic growth in the digital age.
Keywords: Electronic commerce, e-commerce, types of e-commerce, transactional dynamics, B2B, B2C, C2C, C2B, B2A, C2A, benefits of e-commerce, challenges of e-commerce, cybersecurity risks, market growth, digital landscape, global trade, economic development.